MOTIVATIONAL FACTORS, FACILITATORS, OBSTACLES AND GENDER DIFFERENCES: AN EXPLORATORY STUDY OF THAI ENTREPRENEURS - Yukongdi, Vimolwan (PEOPLE: International Journal of Social Sciences, 2018)
The objective of this study is to identify the motives for starting a business, the perceived facilitators, obstacles and gender differences between Thai male and female entrepreneurs. A questionnaire survey was administered to entrepreneurs in Bangkok yielding a total sample of 103 respondents. Data were analyzed using cross-tabulation analysis. The results indicated that for male entrepreneurs, the desire to own a business, opportunity to earn higher income, passion for a product, the desire to be one’s own boss, taking over family business and unemployment were cited most frequently as motivators. Among the female entrepreneurs, the top motives were the desire to own a business, unemployment, the desire to be one’s own boss, passion for a product, the opportunity to increase income, and taking over family business. For women, unemployment appeared to push them to become an entrepreneur, while for men, financial motive was a pull factor. For both men and women, the factors perceived to be facilitators were mainly related to personality traits of perseverance, honesty, diligence and sincerity. Competition, low profitability, adverse economic and weather conditions were viewed as obstacles in running their business for both male and female entrepreneurs in this study. Implications of the study and recommendations for aspiring entrepreneurs are discussed.